Circulo Domoche: making memory and doing methodology as we go - Lira Muñoz, Andrea Cecilia; Luisa Munoz-Garcia, Ana; Loncon, Elisa (My University, 2022)
In this article, we reflect on a research method we called Circulo Domoche, part of a larger research project on the histories of schooling of Mapuche women in Chile in a context of continual violence against Indigenous people. It originates in the personal experience of the researchers with Chilean schooling and our academic work on education. We share our process of methodological exploration for studying the stories of schooling of Mapuche women from multiple generations. The three authors, along with four others, met periodically and wrote each other letters to talk about our memories of schooling to explore ways of doing research that does not reproduce epistemicide and exploitation of Indigenous people through research. Building on theoretical perspectives from Indigenous scholars and scholars of colour we developed a way of making memory while doing research together. We propose thinking of methodology as not structured beforehand but one that grows along with and as the research unfolds. We share here this community construction as resistance to necropolitics as well as what we have learned by creating spaces of refusal within an academy that functions in a different logic of neoliberal regulation of the construction of knowledge.
Keywords: decolonization; refusal; epistemicide